New factors in heart failure pathophysiology: Immunity cells release of extracellular vesicles - Alba Vilella-Figuerola; Alba Vilella-Figuerola; Teresa Padró; Teresa Padró; Eulàlia Roig; Sònia Mirabet; Sònia Mirabet; Lina Badimon; Lina Badimon; Lina Badimon (Frontiers in Cardiovascular Medicine, 2022)
Leukocyte-shed extracellular vesicles (EVs) can play effector roles in the pathophysiological mechanisms of different diseases. These EVs released by membrane budding of leukocytes have been found in high amounts locally in inflamed tissues and in the circulation, indicating immunity cell activation. These EVs secreted by immune cell subsets have been minimally explored and deserve further investigation in many areas of disease. In this study we have investigated whether in heart failure there is innate and adaptive immune cell release of EVs. Patients with chronic heart failure (cHF) (n = 119) and in sex- and age-matched controls without this chronic condition (n = 60). Specifically, EVs were quantified and phenotypically characterized by flow cytometry and cell-specific monoclonal antibodies. We observed that even in well medically controlled cHF patients (with guideline-directed medical therapy) there are higher number of blood annexin-V+ (phosphatidylserine+)-EVs carrying activated immunity cell-epitopes in the circulation than in controls (p < 0.04 for all cell types). Particularly, EVs shed by monocytes and neutrophils (innate immunity) and by T-lymphocytes and natural-killer cells (adaptive immunity) are significantly higher in cHF patients. Additionally, EVs-shed by activated leukocytes/neutrophils (CD11b+, p = 0.006; CD29+/CD15+, p = 0.048), and T-lymphocytes (CD3+/CD45+, p < 0.02) were positively correlated with cHF disease severity (NYHA classification). Interestingly, cHF patients with ischemic etiology had the highest levels of EVs shed by lymphocytes and neutrophils (p < 0.045, all). In summary, in cHF patients there is a significant immune cell activation shown by high-release of EVs that is accentuated by clinical severity of cHF. These activated innate and adaptive immunity cell messengers may contribute by intercellular communication to the progression of the disease and to the common affectation of distant organs in heart failure (paracrine regulation) that contribute to the clinical deterioration of cHF patients.